Stingless bees as collectors of resin from Bertholletia excelsa Bonpland (Lecythidaceae) - Cruz, Iris A.; Barroso, Paulo C. S. (Entomological Communications, 2023)
Stingless bees build their nests using, in general, clay, wax and resins; in addition, these bees also use resins for defense against natural enemies and as an antimicrobial agent. Our goal was to register the stingless bees that collect resin from Bertholletia excelsa, and the observations were made in the Reserva Particular do Patrimônio Natural Dr. Daisaku Ikeda, Manaus, Amazonas, with five species recorded: Melipona (Michmelia) seminigra, Trigona albipennis, Trigona hypogea, Trigona williana, and Ptilotrigona lurida. Bees invest substantial amounts of energy and labor to collect resin from a wide spectrum of different plant species, and the resin must be considered as a necessary resource for the conservation of Amazonian stingless bees.